The Impact of Flow Rate Variations on the Power Performance and Efficiency of Proton Exchange Membrane Fuel Cells: A Focus on Anode Flooding Caused by Crossover Effect and Concentration Loss - Byung-Yeon Seo; Hyun Kyu Suh (Energies, 2025)
This study investigates the effects of anode and cathode inlet flow rates (ṁ) on the power performance of bipolar plates in a polymer electrolyte membrane fuel cell (PEMFC). The primary objective is to derive optimal flow rate conditions by comparatively analyzing concentration loss in the I−V curve and crossover phenomena at the anode, thereby establishing flow rates that prevent reactant depletion and water flooding. A single-cell computational model was constructed by assembling a commercial bipolar plate with a gas diffusion layer (GDL), catalyst layer (CL), and proton exchange membrane (PEM). The model simulates current density generated by electrochemical oxidation-reduction reactions. Hydrogen and oxygen were supplied at a 1:3 ratio under five proportional flow rate conditions: hydrogen (<semantics><mover accent="true">m˙</mover>H2</semantics> = 0.76–3.77 LPM) and oxygen (<semantics><mover accent="true">m˙</mover>O2</semantics> = 2.39–11.94 LPM). The Butler–Volmer equation was employed to model voltage drop due to overpotential, while numerical simulations incorporated contact resistivity, surface permeability, and porous media properties. Simulation results demonstrated a 24.40% increase in current density when raising <semantics><mover accent="true">m˙</mover>H2</semantics> from 2.26 to 3.02 LPM and <semantics><mover accent="true">m˙</mover>O2</semantics> from 7.17 to 9.56 LPM. Further increases to <semantics><mover accent="true">m˙</mover>H2</semantics> = 3.77 LPM and <semantics><mover accent="true">m˙</mover>O2</semantics> = 11.94 LPM yielded a 10.20% improvement, indicating that performance enhancements diminish beyond a critical threshold. Conversely, lower flow rates (<semantics><mover accent="true">m˙</mover>H2</semantics> = 0.76 and 1.5 LPM, <semantics><mover accent="true">m˙</mover>O2</semantics> = 2.39 and 4.67 LPM) induced hydrogen-depleted regions, triggering crossover phenomena that exacerbated anode contamination and localized flooding.